2019
DOI: 10.1136/bmjopen-2019-029420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of the NHS Health Check programme in South England: a quasi-randomised controlled trial

Abstract: ObjectiveTo evaluate uptake, risk factor detection and management from the National Health Service (NHS) Health Check (HC).DesignThis is a quasi-randomised controlled trial where participants were allocated to five cohorts based on birth year. Four cohorts were invited for an NHS HC between April 2011 and March 2015.Setting151 general practices in Hampshire, England, UK.Participants366 005 participants born 1 April 1940–31 March 1976 eligible for an NHS HC.InterventionNHS HC invitation.Main outcome measuresHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
3
19
0
1
Order By: Relevance
“…Like other earlier studies 2009-13, 16 29-34 our 2013-17 study identified more diagnoses of new hypertension, diabetes and chronic kidney disease and higher prescription of statins among NHS Health Check attendees. 35 Our study is the first to report increased diagnoses of atrial fibrillation and dementia resulting from an NHS Health Check. Three previous studies considered atrial fibrillation, and none reported dementia using populations comprised largely of people under age 65 years in which both conditions are rare and hence unlikely to identify changes in diagnosis.…”
Section: Comparison With Existing Literaturementioning
confidence: 71%
See 1 more Smart Citation
“…Like other earlier studies 2009-13, 16 29-34 our 2013-17 study identified more diagnoses of new hypertension, diabetes and chronic kidney disease and higher prescription of statins among NHS Health Check attendees. 35 Our study is the first to report increased diagnoses of atrial fibrillation and dementia resulting from an NHS Health Check. Three previous studies considered atrial fibrillation, and none reported dementia using populations comprised largely of people under age 65 years in which both conditions are rare and hence unlikely to identify changes in diagnosis.…”
Section: Comparison With Existing Literaturementioning
confidence: 71%
“…Three previous studies considered atrial fibrillation, and none reported dementia using populations comprised largely of people under age 65 years in which both conditions are rare and hence unlikely to identify changes in diagnosis. 36 35 Chang 29 found increased atrial fibrillation diagnosis in attendees, which was not significant after matching. Our study used a denominator of age 65 -74 years followed for 12 months and we observed significantly more new diagnosis of atrial fibrillation in attendees 5/1000 than non-attendees 3/1000.…”
Section: Comparison With Existing Literaturementioning
confidence: 91%
“…In 11 studies, 21,23,26,[30][31][32]34,[37][38][39][40] 7 of which were trials, general health checks were associated with small or moderate improvements in measures such as blood pressure, cholesterol, and cardiovascular risk scores. In the Family Heart Study conducted in the U.K. (n=12,924), both women and men randomized to a general health check followed by tailored follow-up had reduced systolic blood pressure (6.4 mmHg reduction for women; 7.4 mmHg for men) and diastolic blood pressure (2.7 mmHg for women; 3.3 mmHg for men) after one year.…”
Section: Risk Factor Controlmentioning
confidence: 99%
“…In four randomized trials 19,24,30,31 and six observational studies, 32-37 detection of chronic disease was increased among patients receiving general health checks. In the recent Check-In Study trial among patients aged 45 to 64 with low levels of education, 5% of patients randomized to a single preventive health check, and 2% of those randomized to usual care, received a new antidepressant prescription over one year.…”
Section: Observationsmentioning
confidence: 99%
“…More common in men M ore common in women Symptom prevalence: Both men and women with confirmed ACS presented most often with chest pain (pooled prevalence men 79% [72-85]; women 74% [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]), diaphoresis (men 47% [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]; women 44% [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]), shortness of breath (men 40% [35][36][37]…”
Section: Chest Painmentioning
confidence: 99%